Identification of patients at higher risk for myocardial injury following elective coronary artery intervention - Abu Sharar, Haitham; Helfert, Stefanie; Vafaie, Mehrshad; Pleger, Sven Torsten; Chorianopoulos, Emmanuel; Bekeredjian, Raffi; Katus, Hugo; Giannitsis, Evangelos (Catheterization and cardiovascular interventions, 2020)
Objectives - To evaluate myocardial injury and infarction (MI) following elective percutaneous coronary intervention (PCI). - - Background - The substantially higher analytical power of high‐sensitivity troponin (hsTn) assays allows detection of minor cardiac troponin (cTn) levels, which may be useful in monitoring myocardial injury and guiding therapies.
First published: 22 October 2019
Gesehen am 26.01.2021